Impact Financial Performance to Stock Price: Evidence from Jordan - Kerroucha Fatima Zohra, (Journal of North African Economies, 2025)
This study examined the effect of market price to book value ratio, Net Profit Margin (NPM), on stock prices of Jordanian banks listed in Amman stock exchange for the period (2018-2020). This research was tested using a T-test tool and Linear-regression and ANOVA methods to prove the proposed hypothesis. The results showed that both market price to book value and net profit margin (NPM) have a significant positive effect on stock prices. The value of financial performance at the Jordanian stock exchange listed banks cost amounts to 73.8 percent, while other unlisted factors in this study represent 26.2 percent.